Effect of a single-session meditation training to reduce stress and improve quality of life among health care professionals: a 'dose-ranging' feasibility study. - Prasad K; Wahner-Roedler DL; Cha SS; Sood A (Alternative Therapies in Health & Medicine)
PRIMARY STUDY OBJECTIVE: The primary aim of the study was to assess the feasibility of incorporating a single-session meditation-training program into the daily activities of healthy employees of a tertiary-care academic medical center. The study also assessed the most preferred duration of meditation and the effect of the meditation program on perceived stress, anxiety, and overall quality of life (QOL). METHODS: POPULATION: Seventeen healthy clinic employees were recruited for this study. INTERVENTION: After an initial group instruction session covering basic information about meditation, Paced Breathing Meditation (PBM) was taught to the participants. Participants were instructed to self-practice meditation with the help of a DVD daily for a total of 4 weeks. The DVD had three different programs of 5, 15, and 30 minutes with a menu option to choose one of the programs. OUTCOME MEASURES: (1) Patient diary, (2) Perceived Stress Scale (PSS), (3) Linear Analogue Self-Assessment (LASA), (4) Smith Anxiety Scale (SAS). Primary outcome measures were compared using the paired t-test. RESULTS: All participants were female; median age was 48 years (range 33-60 y). The 5-minute meditation session was practiced by 14 participants a total of 137 times during the 4-week trial period, the 15-minute session by 16 participants a total of 223 times, and the 30-minute session by 13 participants 71 times. The median number of days practiced was 25 (range 10-28 d); the average total time practiced was 394 minutes (range 55-850 min). After 4 weeks of practice, the scores of the following instruments improved significantly from baseline: PSS (P < .0001), SAS (P = .0005), LASA (P = .0005). No relationship was noted between the length of time practiced and improvement of PSS, SAS, and LASA scores. CONCLUSION: This pilot study indicates the feasibility of teaching meditation in a single training session to health care employees. The study shows that 15 minutes once or twice a day is the most feasible duration of meditation practice. The study also provides promising preliminary efficacy data of this program for improving stress, anxiety, and QOL.